Gambaran Etika Belajar dan Hasil Belajar Mahasiswa Prodi Manajemen Informasi Kesehatan Stikes Santa Elisabeth Medan - Josua Saputra Munthe; Jetslin Simbolon; Selviani Sipayung; Angelia Pasaribu (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
Ethics of study is the activity of seeking knowledge carried out by someone where this activity makes him gain knowledge by paying attention to manners, manners and manners during the teaching and learning process. Ethics of study as moral principles, teachings, habits, or habits about what is good, and appropriate in the implementation of teaching and learning. The more mature humans are, the more difficult it is to pay attention to adab in ethics, especially for students who still do not know the ethics of learning during the teaching and learning process. This study aims to help find out the description of the learning ethics of information management study program students. Health STIKes Santa Elisabeth Medan This research was conducted at STIKes Santa Elisabeth Medan in March using a quantitative method. The subjects of this study were students of the Health Information Management Study Program. While the research object is the Effect of Learning Ethics on Learning Outcomes of Students of the Health Information Management study program, Stikes Santa Elisabeth Medan. The instrument for measuring research variables is to provide a questionnaire. The form of the questionnaire used is a closed questionnaire, in which the respondent chooses the correct answer according to the answer chosen in the research questionnaire. The sampling technique uses quota sampling. The results achieved by students after participating in the teaching and learning process which includes the cognitive, affective and psychomotor domains can be assessed through oral and written tests. Learning ethics in relation to the learning process aims to direct how the actual teaching and learning process with clear rules is expected to produce maximum output, especially students who are knowledgeable and have faith and morality.